Feminist Perspective in Shashi Deshpande’s Selected Novels - Sambharwal, Shree Om; Yadav, Neetu (International Journal of Language and Literary Studies, 2022)
No other woman novelist than Shashi Deshpande has been given accolades so greatly and accorded prominence and worldwide recognition for the projection of feminine sensibility in Indian English Literature. Her exploration of the female psyche by probing deep into the inner working of her mind is highly appreciated by the readers and greatly discussed among the researchers and critics. The novels of Shashi Deshpande are centred on women’s psyche to understand their urges and despairs in a better way. Her protagonists advocate for ‘A Room of One’s Own and proclaim their rights on their bodies. She has portrayed the characters unsatisfied with the uncongenial social conditions that confront their aspirations, needs, urges and hopes. So they conduct themselves in different ways displaying different attitudes and temperaments. These characters undergo a remarkable dynamism in their personalities, and display satisfactory development in their attitude and outlook regarding life. The authors in this research analysis have attempted to examine in depth the various feminist issues projected in her novels through the characters of the main protagonists: Indu of Roots and Shadows, Jaya of That Long Silence and Saru of The Dark Holds No Terrors.